Scheduling And Monitoring of a Case Study of a Commercial Complex (Bansal One) Using Primavera P6 - Jain, Vishesh; Raj, Ravindra Kumar (International Journal of Scientific Research in Civil Engineering, 2022)
Project management is a skill development technique which says that project can be laid on an easy ongoing way to protect the losses and damages occur at site. This technique is very effective in managing big projects where proper management at site is mandatorily required. Construction project manages the projects considering all boundary conditions such as equipment’s, resources, skilled persons, labor, machinery etc. These tools helps in promoting project speed and management of all these equipments lead to a successful project completion in a bounded time duration. In this paper presenting case study scheduling and monitoring using management tool primavera p6